Konstruk Materi Kepemimpinan Islam dalam Perkuliahan PAI di Politeknik Berbasis Kepemimpinan Spiritual dalam Kisah Raja Thalut - Qodratulloh, Waway (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2023)
This article aims to explore and integrate the concept of spiritual leadership into the Islamic Religious Education (PAI) at the Polytechnic as a response to the moral crisis in national leadership. PAI, as a mandatory national subject, holds a strategic position in providing knowledge and understanding to students about the importance of leadership based on spiritual values. With this, it is hoped that students can become leaders who possess moral sensitivity, integrity, and strong leadership competencies in the future. The research approach used is qualitative, where data is collected through interviews, observations, and document studies. The documents explored in this research include the Syllabus, Course Materials, textbooks, and various literature related to the examined theme. Furthermore, an analysis is conducted on the context of the Polytechnic based on Spiritual Leadership, including the understanding of PAI at the Polytechnic and the need for relevant Islamic leadership material constructs. The final step is the development of Islamic leadership material constructs based on spiritual leadership. Studies on the constructs of leadership materials in PAI courses at the Polytechnic are rarely conducted, thus this article overlooks an important initial study that needs to be conducted. This serves as the novelty of this research. The study findings indicate that Islamic leadership in the constructs of course materials can be provided starting with the introduction of (1) the concept of Islamic leadership, (2) the Story of King Saul (Raja Thalut), and (3) the Values of King Saul's Leadership. Course assignments are carried out through (1) Memorizing Surah Al-Baqarah verses 246-252, (2) Leadership Case Analysis, (3) Leadership Simulation, and (4) Collaboration with the industry. Course evaluation is conducted through (1) Written Exams, (2) Individual Assignments, and (3) Group Discussions. Keywords : Leadership, Studi of Islam,Spiritual Leadership